2015
DOI: 10.1016/j.worlddev.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Is the Relationship Between Financial Development and Economic Growth Monotonic? Evidence from a Sample of Middle-Income Countries

Abstract: We revisit the relationship between financial development and economic growth in a panel of 52 middle-income countries over the 1980-2008 period. Using pooled mean group estimations in a dynamic heterogeneous panel setting, we show that there is an inverted U-shaped relationship between finance and growth in the long-run. In the short run, the relationship is insignificant. This suggests that too much finance can exert a negative influence on growth in middle-income countries. The finding of a non-monotonic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
345
4
14

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(387 citation statements)
references
References 107 publications
24
345
4
14
Order By: Relevance
“…They submitted that in the long run, financial development significantly impacted growth. Samargandi, Fidrmuc, and Ghosh (2015) used pooled mean group estimation techniques in a dynamic heterogeneous panel setting to re-examine the connections between economic growth and financial development for a panel of 52 middle-income economies for a period covering 1980-2008, and observed that the relationship between the dual is U-shaped in the long run and insignificant in the short run. The implication is that excessive financial development beyond the optimum economic growth will have an adverse effect on growth.…”
Section: Trade Openness and Economic Growth Nexusmentioning
confidence: 99%
“…They submitted that in the long run, financial development significantly impacted growth. Samargandi, Fidrmuc, and Ghosh (2015) used pooled mean group estimation techniques in a dynamic heterogeneous panel setting to re-examine the connections between economic growth and financial development for a panel of 52 middle-income economies for a period covering 1980-2008, and observed that the relationship between the dual is U-shaped in the long run and insignificant in the short run. The implication is that excessive financial development beyond the optimum economic growth will have an adverse effect on growth.…”
Section: Trade Openness and Economic Growth Nexusmentioning
confidence: 99%
“…For example, Samargandi, et al (2015) use pooled mean group estimations in a dynamic heterogeneous panel setting and demonstrate that there is an inverted U-shaped relationship between finance and growth in the long run. However, as far as we know, no paper has used the same variable settings in the cointegration relationship we are analyzing in this paper.…”
Section: mentioning
confidence: 99%
“…Empirical results in most of the papers provide that there is a statistically significant relationship between growth and financial development indicators (Akinci Yuce, Akinci, and Yilmaz, 2014;Beck et al, 2008;Beck, Georgiadis, and Straub, 2014;Beck et al, 2000;Benhabib and Spiegel, 2000;Calderón and Liu, 2003;Caporale et al, 2015;Chen and Quang, 2014;Chen, Wu, and Wen, 2013;Chow and Fung, 2013;Christopoulos and Tsionas, 2004;Demetriades and Hook Law, 2006;Ductor and Grechyna, 2015;Dwyfor Evans, Green, and Murinde, 2002;Fisman and Love, 2004;Habibullah and Eng, 2006;Hassan, Sanchez, and Yu, 2011;Ketteni et al, 2007;Lartey and Farka, 2011;Lee and Chang, 2009;Levine et al, 2000;Li, Zhang, and Ma, 2015;Wachtel, 2000, 2002;Saci, Giorgioni, and Holden, 2009;Stengos and Liang, 2005;Zhang, Wang, and Wang, 2012). However, in some of the papers, there is no clear consensus on the relationship between financial development and economic growth for all measurements of financial development (Bangake and Eggoh, 2011;Beck and Levine, 2002;Rioja and Valev, 2004;Samargandi, Fidrmuc, and Ghosh, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%